Evaluation of Randomised Controlled Trials Published in Indian Specialty Dental Journals for Statistical Testing of Baseline Differences: A Meta-Epidemiological Study - Mahesh R. Khairnar; PG Naveen Kumar; Ananta Kusumakar; Zainab Akram; Harloveen Sabharwal; Sachin Jadhav (Indian Journal of Dental Research)
Background: In randomised controlled trials (RCTs), the application of a test of significance to compare the baseline differences between the intervention groups is a common practice, though it has been condemned by many researchers. Objective: This study aimed to assess the proportion of RCTs on human participants comparing the baseline differences between intervention groups using the test of significance in nine dental specialty journals published in India and to estimate the proportion of studies reporting baseline demographic and clinical characteristics in a table. Materials and Methods: RCTs published in nine dental journals published by dental specialty associations of India were screened. A literature search was limited to the time duration of five years from 2017 to 2021. Results: The authors analysed 326 RCTs. Of 326 RCTs published, 237 RCTs (72.7%) did not report the baseline demographic and clinical characteristics table. Tests of significance were applied to compare baseline differences between the intervention arms in 148 (45.4%) RCTs published. Conclusions: Although criticised by the Consolidated Standards of Reporting Trials (CONSORT) statement, the majority of the trials published in dental specialty journals failed to avoid comparison of baseline differences with significance test and failed to report baseline characteristic table.